Impact of irrigation regime on trees and turfgrass in a landscape setting - Findley, Douglas Alan, author; Wallner, Stephen J., advisor; Jacobi, William R., committee member; Stushnoff, Cecil, committee member; Koski, Anthony J., committee member (Colorado State University. Libraries, 1999)
The response of Gleditsia tricanthos inermis 'Skyline', Fraxinus pennsylvannica 'Patmore', and Paa pratensis 'Livingston' grown in a landscape setting to three irrigation regimes was evaluated. Irrigation regimes were based on evapotranspiration (ET) and consisted of deficit, (40% ET), replacement, (80% ET), or excessive, (160% ET) amounts of water applied throughout the growing season. These irrigation regimes had no affect on leaf weight, area, percent moisture, height, caliper, or cold hardiness low temperature exotherms (LTE). Leaf water potential of the trees, a measure of plant water stress, was lower with decreasing application of water. Fall color development was affected only for Fraxinus pennsylvannica 'Patmore'. Deficit irrigated trees initiated fall color two weeks earlier and reached maximum fall color one week prior to trees under excessive irrigation. Turfgrass clipping weight and percent moisture was reduced in both studies with decreasing irrigation levels. Turfgrass irrigated at 160% ET remained dark green, and continued growing throughout the summer, producing large quantities of clippings. Replacement irrigated turfgrass maintained a dark green color, highly desired by landscape managers and homeowners, but clipping quantities were significantly reduced compared to excessively irrigated turfgrass. When Paa pratensis was maintained at 40% ET, it entered drought induced dormancy three to six weeks after treatment initiation. The turfgrass was light green, and bare soil was visible through the canopy in some portions of the plots providing an ideal location for weed seeds to germinate. Results from these studies indicate that irrigation regime has a limited affect on tree growth and development after one growing season, however the long term impact after several years of similar irrigation regimes may be more important for disease and insect outbreaks. Turfgrass growth is affected by irrigation regime in such a way that landscape managers can reduce clippings by reducing irrigation levels and still maintain acceptable quality turfgrass.
Covers not scanned.
Keywords: Irrigation -- Management; Turf management; Trees -- Irrigation